Управління ризиком на основі застосування когнітивного моделювання - Ріжок, І. М. (Ways to Improve Construction Efficiency, 2012)
Considered the concept personnel at risk. Improved risk factors personnel. Identified measures to ensure the reliability of personnel. Developed a cognitive map of management of human risk.